Rebecca's garden Spring garden 3 (New York NBC Enterprises, 2003)
Rebecca Kolls teaches the basics of spring gardening as seen on her show Rebecca's Garden. Topics include shopping tips, lawn care, and decorating ideas. Chapters on picking out a lawnmower, planting eggplant, and a recipe for eggplant are included as bonuses. ~ Amanda Van Keuren, All Movie Guide
DVD
1
Keywords: Educational videos; Gardening; DVD-Video disks -- 2003